Bilateral Alterations in Isokinetic Strength and Knee Biomechanics During Side-Cutting 1 Year After Unilateral ACL Reconstruction. Issue 11 (September 2022) - Shi, Huijuan; Ren, Shuang; Huang, Hongshi; Liu, Hui; Liang, Zixuan; Yu, Yuanyuan; Li, Hanjun; Ao, Yingfang
Background: Individuals with anterior cruciate ligament (ACL) reconstruction (ACLR) are a population that has a higher risk for ACL injury compared with the general population. To reduce the reinjury rate and improve the rehabilitation outcome after ACLR, risk factors for ACL injury have to be addressed. Purpose: To compare the knee biomechanics during side-cutting and isokinetic strength of the thigh muscle of the reconstructed leg with those of the contralateral leg and healthy controls and investigate the knee movement asymmetries in individuals with ACLR. Study Design: Controlled laboratory study. Methods: A total of 16 participants with ACLR (ACLR group; 11.8 ± 1.1 months after reconstruction) and 16 healthy controls (control group) were recruited. Landmark coordinates and ground-reaction forces during side-cutting and isokinetic strength of hamstring and quadriceps were collected. Two-way analysis of variance with the mixed design was performed to compare each dependent variable between groups and across legs. Results: The reconstructed leg had a significantly smaller knee flexion angle ( P = .004) and less quadriceps strength ( P = .003) than the contralateral leg. The knee extension moment and knee external rotation angle were decreased compared with both the contralateral leg ( P = .001, P = .003, respectively) and the healthy control leg ( P = .001, P = .001, respectively). The ACLR group showed greater knee abduction angles ( P = .004) and smaller knee external rotation moments ( P = .006) than the control group. The ACLR group also demonstrated greater asymmetries of knee flexion angle ( P = .015), knee external rotation angle ( P = .001), knee extension moment ( P = .013), knee abduction moment ( P = .001), and quadriceps strength ( P = .046) than the control group. Conclusion: Knee biomechanics in the leg with ACLR were altered mainly in the sagittal plane during side-cutting compared with the contralateral leg. The altered movement patterns between the ACLR and control groups were primarily observed in the frontal and transverse planes. The ACLR group also demonstrated greater asymmetries of sagittal knee movement and concentric quadriceps strength than the control group. Clinical Relevance: Individuals with ACLR showed different alterations in the reconstructed and contralateral leg compared with healthy controls. These results suggest that rehabilitation programs after ACLR should further focus on restoring the knee flexion angle and quadriceps strength. Injury prevention programs need to be further targeted in the altered movement patterns observed between the ACLR and the healthy groups.